Protective effects of astragaloside IV against hypertension-induced vascular remodeling involves the DNMT1 and TET2 signaling pathway - Qin, Yingchun; Xie, Yilin; Li, Aihua; Zhang, Xiaoqin; Yan, Zhiqiang (Archives of Biological Sciences, 2021)
Paper description: Astragaloside IV (AS-IV), a triterpene saponin from Astragalus membranaceus, has a beneficial effect in cardiovascular disease. In two-kidney one-clip (2K1C) hypertensive rats, AS-IV: reduced blood pressure; reversed hypertension-induced thoracic media thickness; inhibited DNMT1, MMP2, PCNA; increased SM22α, ACTA2, TET2 expression in the aorta; in vitro it inhibited the proliferation and migration in VSMCs treated with angiotensin II; induced SM22α, ACTA2, TET2; reduced COL-1a, COL-3a, DNMT1, MMP2, PCNA expression; modulated 5-methylcytosine expression. AS-IV reversed hypertension-induced vascular remodeling by inhibiting DNMT1, upregulating TET2. Novel insight for As-IV treatment of vascular disease is provided. Abstract: Proliferation, migration, and the phenotypic switch of vascular smooth muscle cells (VSMCs) play an important role in vascular remodeling induced by hypertension. Astragaloside IV (AS-IV), the active ingredient of Astragalus membranaceus, has been shown to exert a beneficial role in cardiovascular disease. The present study aimed to investigate the mechanism responsible for the protective effects of AS-IV on hypertension-induced vascular remodeling. AS-IV significantly reduced blood pressure and aortic media thickness in two-kidney, one-clip (2K1C) hypertensive rats. AS-IV administration downregulated the expression levels of DNA methyltransferase1 (DNMT1), matrix metalloproteinase (MMP2) and proliferating cell nuclear antigen (PCNA) and upregulated the expression of smooth muscle 22α protein (SM22α), α-smooth muscle actin (ACTA2) and ten-eleven translocation 2 (TET2) in the aorta of hypertensive rats. AS-IV inhibited the proliferation and migration in VSMCs treated with angiotensin II (Ang II). AS-IV increased the expression of SM22α, ACTA2 and TET2, and decreased the expression of collagen Ia (COL-1a), collagen IIIa (COL-3a), DNMT1, MMP2 and PCNA in vitro. Reduction in 5-methylcytosine (5-mC) was observed in VSMCs treated with AS-IV. Knockdown of DNMT1 induced the expression of TET2, while the level of DNMT1 did not change after knockdown of TET2. These results suggest that AS-IV reversed hypertension-induced vascular remodeling by inhibiting DNMT1 and upregulating TET2.